PREVALENCE AND CORRELATES OF DEPRESSION AMONG EVER – MARRIED WOMEN IN A COASTAL PANCHAYAT OF RURAL THIRUVANANTHAPURAM - ANJU LIJIN (ACHUTHA MENON CENTRE FOR HEALTH SCIENCE STUDIES SREE CHITRA TIRUNAL INSTITUTE FOR MEDICAL SCIENCES AND TECHNOLOGY, 2012)
Background: Depression results in much disability, causes premature mortality either from physical disorders or from suicide and is twice more common among women than men. Kerala has one of the highest suicide rates in India. Studies on depression are very limited among young adult women, especially in coastal regions of Kerala which are frequented by floods with dislocation of households. Therefore this study was conducted with an objective to find the prevalence of depression and its associated factors among ever – married women of a coastal grama panchayat in rural Thiruvananthapuram. Methods: A cross sectional survey was carried out among 450 ever – married women (18 – 45 years) selected using multistage cluster sampling. Information on socio-demographic variables, health and reproduction related factors were collected using a pre-tested structured interview schedule. Patient Health Questionnaire 9 depression scale was used to screen for depression and those screened were classified as depressed and not depressed using the score of ten as the cut off. Stepwise backward multiple logistic regression analysis was done to find the predictors of depression. Results: The point prevalence of depression was 24.9 percent. Odds to have screened positive for depression of women aged 30 years and above was more than two times [Odds ratio (OR) 2.61;95 percent Confidence Interval (CI)1.39 – 4.92], those who received education above primary level was half (OR 0.57;CI 0.33 – 0.97), those having gynaecological morbidity was almost three times (OR 2.76;CI 1.68 – 4.52), those who experienced violence from partner in the past one month was almost two times (OR 1.81;CI 1.06 – 3.10) and those whose partners had substance abuse, more than two times (OR 2.62;CI 1.34 – 5.12) compared to their counterparts. Conclusion: Nearly one fourth of the women screened positive for depression which is at a high magnitude keeping in view the prevalence rate of the country and the global estimates. Having any reproductive morbidity, recent experience of domestic violence and substance abuse by husband are found to be associated with depression. Social support at times of need and education above primary level are found to be protective. Efforts to combat the negative factors, measures to encourage education of girls beyond secondary school level and to nurture and enhance community and caregiver support groups may help reduce the prevalence of depression among women in this region.